Fulminant necrotising fasciitis complicating upper limb arteriovenous fistula access for haemodialysis - Sri Satyavathi Davulury; Vinod Bhan (Journal of Clinical and Scientific Research)
Necrotising fasciitis is an aggressive soft-tissue infection with high mortality rates, which needs emergent medical and surgical approach for better results. It is known to occur in drug abusers, immunosuppressed individuals, malignancy, renal failure and in malnourished individuals. It is also described in femoral artery puncture following cardiac catheterisation and access-related complications from secondary infection in pseudoaneurysms following femoral punctures. We report the rare occurrence of upper limb dialysis access with pseudoaneurysms of the cephalic vein with necrotising fasciitis resulting in fulminant gangrene.